NLRP3-Mediated Inflammation in Atherosclerosis and Associated Therapeutics - Lu, Na; Cheng, Weijia; Liu, Dongling; Liu, Gang; Cui, Can; Feng, Chaoli; Wang, Xianwei (Frontiers in Cell and Developmental Biology, 2022)
The NLRP3 inflammasome is a crucial constituent of the body’s innate immune system, and a multiprotein platform which is initiated by pattern recognition receptors (PRRs). Its activation leads to caspase-1 maturation and release of inflammatory cytokines, interleukin-1β (IL-1β) and IL-18, and subsequently causes pyroptosis. Recently, the excess activation of NLRP3 inflammasome has been confirmed to mediate inflammatory responses and to participate in genesis and development of atherosclerosis. Therefore, the progress on the discovery of specific inhibitors against the NLRP3 inflammasome and the upstream and downstream inflammatory factors has become potential targets for clinical treatment. Here we review the recently described mechanisms about the NLRP3 inflammasome activation, and discuss emphatically the pharmacological interventions using statins and natural medication for atherosclerosis associated with NLRP3 inflammasome.